Women in business and their reproductive roles: A study of Maranao women stallholders in Cagayan de Oro City - Bagaporo, Jennefer Lyn L. (Animo Repository, 2003)
The study looks into the Maranao women's participation in business in Cagayan de Oro City and the effects of their participation in business to their reproductive and productive roles. It also describes the background characteristics of the Maramao women stallholders, the reasons for their participation in business, and the support they have received as they carry out their roles as entrepreneurs, mothers and wives. Thirty (30) married, with children, Maranao women aged 15-49 were interviewed using an interview schedule. The Maranao women were divided into two categories: with children age five below and with children age five and above. Results show that the Maranao women engaged in business for two major reasons: 1) to help their husbands in raising and family, and 2) to supply the children with their needs. Their participation in business affected their pregnancy and childbearing, the tasks they perform as wives, and produced both negative and positive consequences on their childcare and rearing. Taking care of the children and allotting time to attend to their needs were impinged by the women's work in the stall. Nevertheless, most of their children were sent to school and the Maranao women stallholders spent most and more of their income on the children. The health-seeking behavior of the Maranao women when they were pregnant and whenever they were sick were also affected by their work in the stall. In terms of decision-making, the Maranao women stallholders were able to make decisions or contribute to decision-making even before they participated in business. This implies that the Maranao women's participation in business is not the only factor that has affected their decision-making involving their reproductive and productive roles. As they perform their responsibilities as mother, wife and entrepreneur support coming from immediate family members, other relatives and non-family members were readily available. Regardless of whether the women stallholders had children aged five below and five